2019
DOI: 10.1038/s41467-019-13266-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cancer sex-disparity in the functional integrity of p53 and its X chromosome network

Abstract: The disproportionately high prevalence of male cancer is poorly understood. We tested for sex-disparity in the functional integrity of the major tumor suppressor p53 in sporadic cancers. Our bioinformatics analyses expose three novel levels of p53 impact on sex-disparity in 12 non-reproductive cancer types. First, TP53 mutation is more frequent in these cancers among US males than females, with poorest survival correlating with its mutation. Second, numerous X-linked genes are associated with p53, including vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 85 publications
4
66
1
Order By: Relevance
“…Unexpectedly, patients with wt TP53 LUSC had significantly reduced survival compared with their mutant TP53 counterparts ( Figure 5 D, p < 0.0001). This was the opposite outcome from LUAD, as we show here ( Figure 1 ), and also to the overall survival in most nonreproductive cancers [ 17 ], where TP53 mutation corresponds with poorest survival. Reduced survival among LUSC patients with wt TP5 3 is a trend for both females and males ( Figure 5 E, p = 0.07 and Figure 5 F, p = 0.17, respectively, with comparably fewer patients with wt TP53 apparently limiting the measurable significance).…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations
“…Unexpectedly, patients with wt TP53 LUSC had significantly reduced survival compared with their mutant TP53 counterparts ( Figure 5 D, p < 0.0001). This was the opposite outcome from LUAD, as we show here ( Figure 1 ), and also to the overall survival in most nonreproductive cancers [ 17 ], where TP53 mutation corresponds with poorest survival. Reduced survival among LUSC patients with wt TP5 3 is a trend for both females and males ( Figure 5 E, p = 0.07 and Figure 5 F, p = 0.17, respectively, with comparably fewer patients with wt TP53 apparently limiting the measurable significance).…”
Section: Resultsmentioning
confidence: 48%
“…Our recent findings demonstrate that for the vast majority of patients with nonreproductive cancers worse survival corresponds with TP53 mutation [17]. In this current study, we sought to test whether this was evident across the major subtypes of NSCLC.…”
Section: Female Luad Patients With Wt Tp53 Status Have the Most Favormentioning
confidence: 88%
See 2 more Smart Citations
“…The T/G allele drives an estrogen-dependent increase in cancer risk in females [249]. A recent study by Haupt et al identified a network of X-linked genes associated with p53 function [250]. They found that mutations in p53 regulatory genes on the X-chromosome were expressed at the mRNA level less frequently in females than in males with the same mutation.…”
Section: Sex Differences In P53mentioning
confidence: 99%